Desenvolvimento e validação de conteúdo de um instrumento para avaliação da assistência farmacêutica em hospitais de Sergipe - Jesus, Elisdete Maria Santos de (2013)
As part of the health services, pharmaceutical services consist in the supply of drugs, maintenance, quality control, safety, therapeutic efficacy, as well as monitoring and evaluation of its use by subsidizing the guarantee rational use. However, since 1992, Brazilian authorities point to the need for tools that allow evaluating pharmacy services in hospitals inserted, making it necessary to perform diagnostic pharmaceutical services at all levels of health care. Given the above this thesis was aimed to develop and validate the content of an instrument for evaluation of pharmaceutical care in hospitals of Sergipe. Therefore a study of type Evaluative Research in Health Initially, we conducted a survey on the theoretical evaluation of the quality of health services, with emphasis on pharmaceutical care services, and the conceptual aspects involved in the validation of a measuring instrument. The practical section was developed with a systematic review of the pharmaceutical services that utilized the psychometric characteristics of reliability and validity and content validation procedure for an instrument using the Delphi technique. In validation strategy content, which was found after analysis and opinion of the evaluators (judges) of the 60 indicators proposed assessment, four experienced changes between standard and compliance elements of measurement. After the modifications, the instrument was administered, applicability of the results showed that 94% of hospital pharmacists understand the questions posed in the instrument, however 33.3% of pharmacists chose not to answer the item related to service pharmacotechnics hospital for not being inserted or structured in some of the hospitals assessed. In parameter suggestion only 11.1% suggested change in the structure of the instrument, the doubts about the instrument in general, 100% of pharmacists said they have no doubts about the proposed questions. This study contributed to improving the quality of hospital pharmacy through content validation process, underscores the importance of further studies to determine the reliability of this instrument, which is to determine the degree of consistency with which the instrument measures the attribute under study.